Hubungan Riwayat Penyakit Infeksi dengan Ststus Gizi Pada Balita Usia 12- 59 Bulan di Puskesmas Oepoi Kota Kupang - Elisabeth Gladiana Cono (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2021)
Infection often occurs in children under five, due to poor nutritional status. It is directly influenced by the lack of knowledge about nutritious source. Vice versa, infection diseases can lead to poor nutritional status in children under five. This study almed to analize the correlation between infection disease and nutritional status in children under five.This was a quantitative study with case-control approach, conducted in Puskesmas Oepoi. Atotal of 106 samples were selected by purposive sampling. Data were collected by a set of questionnaires. Data analyzed by chi- square.This study shows that there is a correlation between infection disease and nutritional status (ρ value=<0.001) and it is statistically significant.It is important to ensure that children is raised by a good parenting and good nutritional pattern, and to keep healthy environment so that children is safe from infectious disease that will lead to poor nutritional status. Keywords:infectious, nutrition, children.